Programming gene expression with combinatorial promoters - Cox, Robert Sidney; Surette, Michael G; Elowitz, Michael B (Molecular systems biology, 2007)
Promoters control the expression of genes in response to one or more transcription factors (TFs). The architecture of a promoter is the arrangement and type of binding sites within it. To understand natural genetic circuits and to design promoters for synthetic biology, it is essential to understand the relationship between promoter function and architecture. We constructed a combinatorial library of random promoter architectures. We characterized 288 promoters in Escherichia coli , each containing up to three inputs from four different TFs. The library design allowed for multiple −10 and −35 boxes, and we observed varied promoter strength over five decades. To further analyze the functional repertoire, we defined a representation of promoter function in terms of regulatory range, logic type, and symmetry. Using these results, we identified heuristic rules for programming gene expression with combinatorial promoters. Synopsis We have investigated the relationship between promoter architecture and gene expression using a combinatorial promoter library. Here, the placement, affinity, and sequence of known binding sites were systematically varied (Figure 1 ), allowing us to determine the range of functions encoded by the simplest combinatorial promoters. Promoters were assembled by ligating oligonucleotides corresponding to 16 variants of each of three promoter regions: distal , proximal , and core . Of the 16 variants of each promoter region, 11 contained binding sites to one of four transcription factors (TFs); the remaining five variants contained no binding sites. The four TFs investigated were the activators AraC and LuxR and the repressors LacI and TetR. Promoters could thus contain up to three binding sites for different TFs. All assembled promoters were linked to luciferase gene expression. A subset of 288 randomly chosen promoters were sequenced, and their expression patterns were probed over all 16 combinations of the four inducers. This approach reveals fundamental features of the relationship between promoter architecture and function. Promoters that responded to a single input were analyzed in terms of their fold‐induction. Promoters that responded to two inputs were examined in terms of their dynamic range, logic type, and symmetry of the response. We summarize the main findings in a set of five heuristic rules for promoter design. Because of the continuous nature of the output levels in each input state, Boolean logic does not accurately represent all possible promoter functions. Therefore, we introduced an intuitive three‐dimensional logic parameterization for the space of promoter functions. In this scheme, we represented promoter phenotypes with three numerical parameters that quantify dynamic range, logic type, and asymmetry (Figure 4 ). We define r as the ratio of the maximum to minimum expression level. Second, the parameter l quantifies the logical behavior of the gate: from pure OR ( l =0) to pure AND logic ( l =1). Third, the parameter a quantifies the asymmetry of the gate with respect to its two inputs. At a =0, the gate responds symmetrically to either inducer, whereas at a =1, the promoter responds only to a single input. The library contained two classes of dual‐input gates. The repressor–repressor (RR) promoters contained operators for the two repressors LacI and TetR, whereas the activator–repressor (AR) promoters responded to the activator AraC and one of the repressors. These two classes of dual‐input gates exhibited differing, but overlapping, distributions of logical phenotypes. Combinatorial synthesis of synthetic promoters permits systematic perturbation of promoter architecture and rapid identification of sequences that implement specific functions. The spectrum of promoter functions observed here highlights following heuristic rules for promoter design. (1) Unlimited regulation—regulated promoter activity is independent of unregulated activity. (2) Repression trend—the effectiveness of repression depends on the site with core ⩾ proximal ⩾ distal . Following this trend, RR promoters may be symmetric or asymmetric. (3) One is enough—full repression is possible with a single operator between −60 and +20. Activators function only upstream of −35 ( distal ) and have little effect downstream ( core or proximal ). (4) Repression dominates activation, producing asymmetric AR promoter logic. (5) Operator proximity—separation of input variables generates SLOPE and asym‐SLOPE logic only. Moving operators closer together makes the logic more AND‐like. Promoter response to combinatorial regulation is more diverse than can be described by Boolean logic. A set of three logic‐phenotype parameters quantitatively captures the behavior of dual‐input promoters. We constructed a combinatorial library of promoters that respond to four inputs. We related promoter sequences within the library to their functions. Critical factors for understanding regulatory logic include transcription factor operator location, spacing, and type (repressor or activator). The combinatorial library reveals heuristic rules for understanding and designing combinatorial promoter logic.